1981
DOI: 10.1037/0022-006x.49.6.807
|View full text |Cite
|
Sign up to set email alerts
|

Use of neuropsychological tests to predict adult patients' everyday functioning.

Abstract: Neuropsychological testing has a unique and important role in (a) delineating the behavioral consequences of brain lesions and (b) predicting the likely impact of such ability deficits on everyday functioning. Here we review the available studies that relate neuropsychological test scores to aspects of self-care and independent living, academic achievement, and vocational functioning. The results are generally positive, but the clinical value of these studies is limited by the fact that most used only intellig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
160
0
1

Year Published

1983
1983
2010
2010

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 300 publications
(168 citation statements)
references
References 23 publications
7
160
0
1
Order By: Relevance
“…In general, if a person shows NP impairment on tests of a certain ability, he0she would be considered at risk for failure in everyday tasks that require the same ability (Heaton & Pendleton, 1981). Perhaps not surprisingly, we found that the NP deficits which best predicted failures on standardized tests of IADLs, were those that also are most commonly observed among cognitively impaired HIV1 participants.…”
Section: Discussionmentioning
confidence: 54%
“…In general, if a person shows NP impairment on tests of a certain ability, he0she would be considered at risk for failure in everyday tasks that require the same ability (Heaton & Pendleton, 1981). Perhaps not surprisingly, we found that the NP deficits which best predicted failures on standardized tests of IADLs, were those that also are most commonly observed among cognitively impaired HIV1 participants.…”
Section: Discussionmentioning
confidence: 54%
“…The total time to complete the test was taken as the test score. (2) The Wisconsin Card Sorting Test (WCST; Heaton and Pendleton, 1981). This assesses abstract thinking, cognitive flexibility, concept identification, hypothesis generation, and the ability to use response feedback information.…”
Section: Neuropsychological Testsmentioning
confidence: 99%
“…However, in a recent review of 15 studies, Bauer and colleagues (26) found that, except for ongoing depressive symptoms, few of these factors were consistently associated with poor functional outcomes across studies. Neurocognitive functioning, remarkably, was not examined in most of the preceding studies of BPD patients, despite having been explored extensively in relation to functional disability in patients with schizophrenia and other neuropsychiatric conditions (17)(18)(19)(20)(21)27).…”
mentioning
confidence: 99%